1997
DOI: 10.1105/tpc.9.11.1963
|View full text |Cite
|
Sign up to set email alerts
|

Aux/IAA proteins repress expression of reporter genes containing natural and highly active synthetic auxin response elements.

Abstract: A highly active synthetic auxin response element (AuxRE), referred to as DR5, was created by performing site-directed mutations in a natural composite AuxRE found in the soybean GH3 promoter. DR5 consisted of tandem direct repeats of 11 bp that included the auxin-responsive TGTCTC element. The DR5 AuxRE showed greater auxin responsiveness than a natural composite AuxRE and the GH3 promoter when assayed by transient expression in carrot protoplasts or in stably transformed Arabidopsis seedlings, and it provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
1,229
1
12

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,596 publications
(1,278 citation statements)
references
References 19 publications
24
1,229
1
12
Order By: Relevance
“…Several studies have indicated that activity of the synthetic consensus auxin reporter, DR5::GUS, closely reflects the auxin induced gene expression in plant tissues. 28,29 The root tips were excised at 4 DAG from DR5::GUS transgenic seedlings and roots were stained for GUS activity 24 h after excision, using a protocol described in Santisree et al 30 In root tip decapitated seedlings, DR5::GUS activity was localized in the pericycle region associated with the primordia of emerging lateral roots (Fig. 1).…”
mentioning
confidence: 99%
“…Several studies have indicated that activity of the synthetic consensus auxin reporter, DR5::GUS, closely reflects the auxin induced gene expression in plant tissues. 28,29 The root tips were excised at 4 DAG from DR5::GUS transgenic seedlings and roots were stained for GUS activity 24 h after excision, using a protocol described in Santisree et al 30 In root tip decapitated seedlings, DR5::GUS activity was localized in the pericycle region associated with the primordia of emerging lateral roots (Fig. 1).…”
mentioning
confidence: 99%
“…[14] This DR5::GUS line carries the b-glucuronidase (GUS) reporter gene, which is under the control of an auxin-responsive DR5 promoter. This reporter line is highly sensitive and specific to biologically active auxins and the GUS reporter enzyme expression is tightly regulated by intracellular auxin in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…The transgenic Arabidopsis reporter line DR5::GUS was previously described. [14] Suspension-cultured transgenic tobacco BY-2 cells, DR5::GFP and GFP-Talin lines [15,17] were maintained in modified MS medium (4.3 g L À1 Murashige and Skoog salts (Duchefa, Haarlem, The Netherlands), 30 g L À1 sucrose, 200 mg L À1 KH 2 PO 4 , 100 mg L À1 inositol, and 1 mg L À1 thiamine, pH 5.8) as described previously [18] on a rotary shaker (150 rpm) at 25 8C in the dark.…”
Section: Quantum Yield Determinationmentioning
confidence: 97%
“…Figure 8 shows data indicating auxin production in N. crassa, which had been observed previously as well (63). Transgenic Arabidopsis thaliana plants expressing the DR5::GUS fusion protein (37,64) were incubated either with water (Fig. 8A), with 100 M IAA (Fig.…”
Section: Fig 7 Qrt-pcr Resultsmentioning
confidence: 99%